2017
DOI: 10.1590/1807-1929/agriambi.v21n5p350-355
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of safflower grains. Part II: Volumetric shrinkage

Abstract: A B S T R A C TAgricultural products usually have their size reduced during the drying process. The quantification of the reduction in the dimensions is important for the development and optimization of equipment for the post-harvest of the product. The aim of the present study was to evaluate the effect of the variation in the moisture content during drying on the volumetric shrinkage of safflower grains and their respective axes. Safflower grains were harvested with an initial moisture content of approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Note that the coffee beans showed a volumetric reduction of ~20% in relation to the initial volume for the moisture content ranging from 1.13 to 0.07(decimal, d.b.). The results found in this study are in line with those observed byMartins et al (2017) for sunflower grains. In this work, the authors verified a volumetric contraction of 16% during drying, for moisture contents varying between 0.45 and 0.08(decimal, d.b.).…”
supporting
confidence: 93%
“…Note that the coffee beans showed a volumetric reduction of ~20% in relation to the initial volume for the moisture content ranging from 1.13 to 0.07(decimal, d.b.). The results found in this study are in line with those observed byMartins et al (2017) for sunflower grains. In this work, the authors verified a volumetric contraction of 16% during drying, for moisture contents varying between 0.45 and 0.08(decimal, d.b.).…”
supporting
confidence: 93%
“…Excessive rain and high humidity after physiological maturity of the seed may cause sprouting in the head. Safflower seeds are small, i.e., thousand-grain mass varies from 55.30 g to 41.30 g [191]. For a proper seed germination, both ploughing and harrowing are required.…”
Section: Safflower Main Featuresmentioning
confidence: 99%
“…Agricultural products show significant changes in their physical properties, including size and shape, when subjected to conditions capable of modifying their moisture (OBA et al, 2019). Understanding these physical properties is of paramount importance for the execution and planning of post-harvest stages (MARTINS et al, 2017a).…”
Section: Resultsmentioning
confidence: 99%
“…Reducing the amount of water in the material reduces the biological activity and physicochemical changes that occur in the post-harvest period (CARVALHO et al, 2022). Knowledge of the physical properties of agricultural products is of fundamental importance for the development and optimization of equipment for post-harvest (MARTINS et al, 2017a). According to Ramashia et al (2018), the knowledge of the physical properties of agricultural products are essential for reducing costs and preserving them during post-harvest.…”
Section: Introductionmentioning
confidence: 99%